Design of Intelligent Integrated Simulation for Marine Electric Propulsion System. Issue 1 (February 2021) - Chen, Xiaomi; Hao, Chunxue
Abstract: Based on integrated simulation technology of both marine electric propulsion system and artificial intelligence, a design of intelligent integrated simulation system of marine electric propulsion based on artificial neural network, fuzzy comprehensive evaluation and fuzzy neural network is proposed in this paper. The intelligent module mainly consists of a nonlinear simulation model, simulation evaluation and model optimization. Thanks to adopting an intelligent module, the accuracy of the simulation system is improved. The software implementation of intelligent integrated simulation for marine electric propulsion system is also discussed. The intelligent integrated simulation system of the marine electric propulsion system can guide the related design of electric propulsion system. The design of intelligent integrated simulation system of marine electric propulsion system can also guide the intelligent integrated simulation design of other systems.